2003
DOI: 10.1093/hmg/ddg051
|View full text |Cite
|
Sign up to set email alerts
|

Usher syndrome type I G (USH1G) is caused by mutations in the gene encoding SANS, a protein that associates with the USH1C protein, harmonin

Abstract: Usher syndrome type I (USH1) is the most frequent cause of hereditary deaf-blindness in humans. Seven genetic loci (USH1A-G) have been implicated in this disease to date, and four of the corresponding genes have been identified: USH1B, C, D and F. We carried out fine mapping of USH1G (chromosome 17q24-25), restricting the location of this gene to an interval of 2.6 Mb and then screened genes present within this interval for mutations. The genes screened included the orthologue of the Sans gene, which is defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
136
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(139 citation statements)
references
References 25 publications
2
136
0
1
Order By: Relevance
“…Parallels between the IMAC and tip-link complex have also allowed exploration of how specific mutations lead to disease in Usher syndrome patients. For example, the L48P substitution associated with Type 1G Usher syndrome impacts a conserved residue in the N-terminal ankyrin repeats of SANS, 48 although the functional effect of this mutation remained unclear. By expressing this mutation in the IMAC functional homolog, ANKS4B, in the context of the CACO-2 BBE intestinal epithelial model system, investigators were able to determine that L48P disrupts targeting of this protein to the apical domain.…”
Section: Discovery Of the Imac Provides Insight On The Basis Of Humanmentioning
confidence: 99%
“…Parallels between the IMAC and tip-link complex have also allowed exploration of how specific mutations lead to disease in Usher syndrome patients. For example, the L48P substitution associated with Type 1G Usher syndrome impacts a conserved residue in the N-terminal ankyrin repeats of SANS, 48 although the functional effect of this mutation remained unclear. By expressing this mutation in the IMAC functional homolog, ANKS4B, in the context of the CACO-2 BBE intestinal epithelial model system, investigators were able to determine that L48P disrupts targeting of this protein to the apical domain.…”
Section: Discovery Of the Imac Provides Insight On The Basis Of Humanmentioning
confidence: 99%
“…Another element of the Usher syndrome-related protein complex is SANS (scaffold protein containing ankyrin repeats and SAM domain). SANS was identified in the site of the Usher 1G mutation [37]. SANS has been localized to the apical portion of the hair cell rather than the stereocilia, and interacts with harmonin [37].…”
Section: Stereociliary Bundlementioning
confidence: 99%
“…SANS was identified in the site of the Usher 1G mutation [37]. SANS has been localized to the apical portion of the hair cell rather than the stereocilia, and interacts with harmonin [37]. Cadherins CDH23 and PCDH15 form extracellular linkages within the hair bundle.…”
Section: Stereociliary Bundlementioning
confidence: 99%
“…The gene encoding Sans was shown to be mutated in Usher syndrome 1G patients and Jackson shaker mutant mice [43,84]. In Jackson shaker mice, hair bundles are disrupted and mice display cochlear and vestibular defects.…”
Section: Sans (Ush1g)mentioning
confidence: 99%
“…In Jackson shaker mice, hair bundles are disrupted and mice display cochlear and vestibular defects. In addition to identifying Sans as the mutated protein in Usher syndrome 1G, Weil et al [84] demonstrated that Sans associates with harmonin. Adato et al [1] also probed the possible interactions of Sans with all of the known Usher proteins and demonstrated that, in addition to harmonin, Sans can bind to itself and myosin 7a, tying it into the complex of usher proteins.…”
Section: Sans (Ush1g)mentioning
confidence: 99%